2004
DOI: 10.1183/09031936.04.00133603
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil degranulation status in allergic rhinitis: observations before and during seasonal allergen exposure

Abstract: Despite the fact that extensive degranulation is a likely prerequisite for a pathogenic role of eosinophils, little is known about the degranulation status of these cells in eosinophilic conditions. The present study of the ultrastructure of tissue eosinophils explores eosinophil degranulation in allergic rhinitis before and during seasonal allergen exposure.A total of 23 patients scored symptoms q.d., prior to and during the pollen season. The numbers of mucosal eosinophils and their degranulation status were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 36 publications
7
48
0
1
Order By: Relevance
“…However, because lung cell counts involve the whole digested organ the marked increase in MIL4 ϩ granulocytes in tissue homogenates seen in the chronic stage of infection likely includes these cells accumulating in airways associated with secondary lesions, as demonstrated above by immunohistochemistry. The pathogenesis of small airway inflammation in general is unclear but it may represent the transmigration of senescent inflammatory cells as a normal process of resolving inflammation (31). The significance of this process in the pathogenesis of tuberculosis may be more complicated, however, because the accumulation of granulocytes in the small airways was often observed in concert with It is unknown as yet whether the loss of T cells in the lungs and the subsequent increase in B cells and MIL4 ϩ granulocytes are related or just coincidental.…”
Section: Discussionmentioning
confidence: 99%
“…However, because lung cell counts involve the whole digested organ the marked increase in MIL4 ϩ granulocytes in tissue homogenates seen in the chronic stage of infection likely includes these cells accumulating in airways associated with secondary lesions, as demonstrated above by immunohistochemistry. The pathogenesis of small airway inflammation in general is unclear but it may represent the transmigration of senescent inflammatory cells as a normal process of resolving inflammation (31). The significance of this process in the pathogenesis of tuberculosis may be more complicated, however, because the accumulation of granulocytes in the small airways was often observed in concert with It is unknown as yet whether the loss of T cells in the lungs and the subsequent increase in B cells and MIL4 ϩ granulocytes are related or just coincidental.…”
Section: Discussionmentioning
confidence: 99%
“…These gross alterations within secretory granules, indicative of progressive release of their products, are described in a diversity of cell types [7,39,40,54]. In human eosinophils, it is recognized that the number of emptying granules increases in activated cells, in vivo and in vitro, in different conditions [33][34][35][36]43]. Inflammatory stimuli, such as chemokines (eotaxin and RANTES) or platelet-activating factor, trigger PMD, and pretreatment with BFA, a potential inhibitor of vesicular transport [55], inhibits agonist-induced, granule emptying [43].…”
Section: Intracellular Distribution and Formation Of Tubular Carriersmentioning
confidence: 99%
“…PMD is a general secretion process implicated in the release of products from activated eosinophils in a range of human diseases including allergic inflammation [33][34][35][36][37]. PMD has also been identified extensively in other secretory cells [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Eosinophil-derived mediators including eosinophilic cationic protein (ECP) damage the epithelium leading to the final clinical and pathological AR findings [1, 13, 14]. It has been reported that mucosal allergic activity is correlated with serum and local mucosal ECP levels [12]. However, the relationship between levels of inflammatory cells or markers with clinical severity is controversial [4].…”
Section: Introductionmentioning
confidence: 99%
“…AR is induced by an IgE-mediated inflammatory reaction following allergen exposure and is characterized by eosinophil infiltration and degranulation [4, 11, 12]. Eosinophil-derived mediators including eosinophilic cationic protein (ECP) damage the epithelium leading to the final clinical and pathological AR findings [1, 13, 14].…”
Section: Introductionmentioning
confidence: 99%